Treatment patterns and primary reasons for adjusted treatment in older and younger patients with stage II or III colorectal cancer. Issue 7 (July 2021) - Scheepers, E.R.M.; Schiphorst, A.H.; van Huis-Tanja, L.H.; Emmelot-Vonk, M.H.; Hamaker, M.E.
Abstract: Objective: This study aims to assess age-related treatment patterns and primary reasons for adjusted treatment in patients with colorectal cancer. Methods: Patients with colorectal cancer stage II or III diagnosed between 2015 and 2018 in the Netherlands were eligible for this study. Data were provided by the Netherlands Cancer Registry and included socio-demographics, clinical characteristics, treatment patterns and primary reasons for adjusted treatment. Treatment patterns and reasons for adjusted treatment were analysed according to age groups. Results: Of all 29, 620 patients, 30% were aged <65 years (n = 8994), 34% between 65 and 75 years (n = 10, 173), 27% between 75 and 85 years (n = 8102) and 8% were ≥85 years (n = 2349). Irrespective of cancer location or stage, older patients received less frequently a combination of surgery and (neo)adjuvant therapy compared to younger patients (decreasing from 55% to 1% in colon cancer patients, and from 71% to 23% in rectal cancer patients aged <65 years and ≥85 years respectively). Omission of surgical treatment increased with age in both patients with colon cancer (ranging from 1% in patients aged <65 years to 16% in those ≥85 years) and rectal cancer (ranging from 12% in patients aged <65 years to 56% in those ≥85 years). The most common reasons for adjusted treatment were patient preference (27%) and functional status (20%), both reasons increased with advancing age. Conclusions: Guideline non-adherence increased with advancing age and omission of standard treatment was mainly based on patient preference and functional status. These findings provides insight in the treatment decision-making process in patients with colorectal cancer. Future research is necessary to further assess patient's role in the treatment decision-making process.